2007
DOI: 10.1007/s10584-007-9367-8
|View full text |Cite
|
Sign up to set email alerts
|

Accumulated winter chill is decreasing in the fruit growing regions of California

Abstract: We examined trends in accumulated winter chill across the fruit growing region of central California and its internal coastal valleys. We tested the hypothesis that global warming is in motion in California and is causing accumulated winter chill to decrease across the fruit and nut growing regions of California. The detection of potential trends in accumulated winter chill (between 0 and 7.2°C) was determined using two complementary climate datasets. The California Irrigation Management Information System (CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
116
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 166 publications
(123 citation statements)
references
References 27 publications
(33 reference statements)
3
116
0
1
Order By: Relevance
“…Numerous phenological studies have identified important direct effects of warming, such as earlier onset of spring plant growth and delayed onset of autumn senescence across temperate mid-latitude climates (Parmesan and Yohe, 2003;Root et al, 2003;Menzel et al, 2006;Schwartz et al, 2006). Yet, many woody plant species growing in these regions also paradoxically require a certain amount of exposure to cold temperatures (termed the fall/winter chilling requirement), in order to properly break their dormancy and be ready to respond to springtime warming (Sarvas, 1974;Cannell and Smith, 1983;Chuine and Cour, 1999;Baldocchi and Wong, 2008;Luedeling et al, 2009 Thus, with recent and projected future warming, a point will eventually be reached (likely different for every species), where plants in temperate climates will no longer be able to continue linearly expanding both ends of their growing season. It is highly likely that temperate plant species in many regions, especially those on the warmer (southern) extremes of their range, may already be inadequately chilled and no longer responding in the same way to additional spring warming (Zhang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous phenological studies have identified important direct effects of warming, such as earlier onset of spring plant growth and delayed onset of autumn senescence across temperate mid-latitude climates (Parmesan and Yohe, 2003;Root et al, 2003;Menzel et al, 2006;Schwartz et al, 2006). Yet, many woody plant species growing in these regions also paradoxically require a certain amount of exposure to cold temperatures (termed the fall/winter chilling requirement), in order to properly break their dormancy and be ready to respond to springtime warming (Sarvas, 1974;Cannell and Smith, 1983;Chuine and Cour, 1999;Baldocchi and Wong, 2008;Luedeling et al, 2009 Thus, with recent and projected future warming, a point will eventually be reached (likely different for every species), where plants in temperate climates will no longer be able to continue linearly expanding both ends of their growing season. It is highly likely that temperate plant species in many regions, especially those on the warmer (southern) extremes of their range, may already be inadequately chilled and no longer responding in the same way to additional spring warming (Zhang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It is highly likely that temperate plant species in many regions, especially those on the warmer (southern) extremes of their range, may already be inadequately chilled and no longer responding in the same way to additional spring warming (Zhang et al, 2007). Therefore, comprehensive assessment of likely plant species responses (growing season change) to continued warming in temperate mid-latitude climates must include the potential impacts of insufficient chilling (Baldocchi and Wong, 2008;Luedeling et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Perennial fruit production systems, which are long-term operations that depend on seasonally low temperatures, may thus be among the agricultural or horticultural systems that are most vulnerable to climate change (Blanke 2008;Cannell et al 1989;Seguin 2003). In a recent study, Baldocchi and Wong (2008) have investigated trends in chilling conditions in California, finding a pronounced decrease in the number of chilling hours at most sites. While they expect these changes to have deleterious consequences by the end of the twenty-first century, other regions might feel detrimental effects of reduced winter chill at a much earlier date.…”
Section: Introductionmentioning
confidence: 99%
“…In many parts of the world, fruit growers use winter chill models to identify appropriate tree cultivars for their production sites. This practice is common in most subtropical growing regions, such as Israel (Erez et al 1979), South Africa (Linsley-Noakes and Allan 1994), Spain (Ruiz et al 2007) and California (Baldocchi and Wong 2008). Growers in these regions generally know very well how much …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation